PENGEMBANGAN MODEL KOMPENSASI BERBASIS KOMPETENSI DI UNIVERSITAS TERBUKA - Amalia Kusuma Wardini (Jurnal Organisasi Dan Manajemen, 2007)
The transformation into stated-owned legal body (BHMN/BHP) makes quite a significant impact on UT management, since the autonomy is wider and consequently it brings bigger responsibilities and challenges. One of these challenges is adjusting compensation system which previously referred to Civil Servants System and currently has several weaknesses, such as externally less competitive salary level, very close gap between highest and lowest salary and minimal concern about performance. It leads to the need of designing new compensation system during UT-BHP transitional period (2008-2017). Competency based Pay (CbP) which is rewarding the way people work, not just recognizing what they can be deliver, fits the academic world. In a learning organization, colleges and universities certainly qualify, the focus on competence and the importance of individual growth is tied explicitly to the organization?s mission and value also consistent with the growing interest in life long learning. The acceptance of individual development and skill acquisition as the criteria for rewarding staff employees should be a natural in higher education. This compensation design is focused on academic staffs, which are lecturer, researcher, and managerial position. Base salary and allowances have several alternatives, and choice will be made based on UT-BHP financial condition and the suitability with UT-BHP human resources development strategy